Eficiência de lambda-cialotrina no controle da broca-do-fruto e aspectos quali-quantitativos da pulverização na cultura da pinha - Morais, Jacqueline Lavinscky Costa; Castellani, Maria Aparecida; Raetano, Carlos Gilberto [UNESP]; de Macêdo, Juliana Alves; Nery, Moisés Silva; Moreira, Gabriela Luz Pereira (FapUNIFESP (SciELO), 2016)
In Brazil, the state of Bahia is one of the largest pinecone (Annona squamosa L.) growers; nevertheless, fruit borer (Cerconota anonella L.) presence limits production. This research aimed to test the efficiency of lambda-cyhalothrin in controlling fruit borer using different spray volumes; additionally, this research tested qualitative and quantitative operational aspects. Trials were carried out in pinecone orchards in Caraíbas-BA, Brazil. Pesticide efficiency was tested by a randomized block experiment with six treatments and five replications. Treatments consisted of lambda-cyhalothrin application (1.5 g a.i. 100 L-1 water) with a surfactant (0.03% v v-1) at spray volumes of 100, 200, 268, 382 and 488 L ha-1 and one control (without spray). Pest infestation was assessed by counting symptomatic fruits for further percentage calculation. Five treatments with five replications were developed to evaluate spraying performance. These treatments consisted of an aqueous solution with a Brilliant Blue tracer at 0.15% (p v-1) and a surfactant at 0.03% (v v-1), using the same spray volumes as the first experiment. Qualitative assessments were performed on water-sensitive paper cards and were quantified through tracer deposit levels on leaves. Spray volumes between 100 and 382 L ha-1 with lambda-cyhalothrin were efficient to control Cerconota anonella in the pinecone crop, providing good quality application.
Lambda-cyhalothrin efficiency on fruit borer control and qualiquantitative spraying aspects in a pinecone crop
Keywords: Annona squamosa; Cerconota anonella; Spray application technology; Tracer